The divine Christology of the Apostle Paul: retrospect and prospect - Bruno, Chris (InterVarsity Press, 2024)
Filled with helpful charts, appendixes, and study aids, this essential guide explores the detailed and often perplexing conversations concerning Paul's view of the divinity of Christ, bringing guidance and clarity to scholars' various articulations, including Larry Hurtado, Chris Tilling, N. T. Wright, and more.